2010
DOI: 10.12775/llp.2010.005
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive logic framework for conditional obligations and deontic dilemmas

Abstract: Lou Goble proposed powerful conditional deontic logics (CDPM) that are able to deal with deontic conflicts by means of restricting the inheritance principle. One of the central problems for dyadic deontic logics is to properly treat the restricted applicability of the principle "strengthening the antecedent". In most cases it is desirable to derive from an obligation A under condition B, that A is also obliged under condition B and C. However, there are important counterexamples. Goble proposed a weakened rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 15 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…This paper fits within the larger project of adaptive deontic logics devised for consistently accommodating normative conflicts (see e.g. [7,29,39,41]). It improves on earlier work presented in [6].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…This paper fits within the larger project of adaptive deontic logics devised for consistently accommodating normative conflicts (see e.g. [7,29,39,41]). It improves on earlier work presented in [6].…”
Section: Introductionmentioning
confidence: 82%
“…In [40] factual detachment is defeasibly applied to O(A B) and B in order to derive the non-conditional obligation OA. Similarly, in [39] strengthening the antecedent is applied to O(A B) defeasibly in order to derive O(A B ∧ C).…”
Section: Adaptive Deontic Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…There too, SDL gives rise to explosion in view of formulas of the form OA ∧ O¬A, OA ∧ P¬A, etc. And there too, authors have suggested weakening the logic in order to tolerate normative conflicts; for some examples, see [12,21,25,28,31,32]. A good oversight can be found in [13].…”
Section: Normative Conflictsmentioning
confidence: 99%
“…Prominent examples are inconsistency ALs (e.g., [4]) or applications to abduction (e.g., [22]) and induction (e.g., [2]). Recent research has shown a growing interest in ALs that tackle various problems with deontic logics (see [6,23,31,29]). …”
Section: A Short Introduction Into Adaptive Logicsmentioning
confidence: 99%